PENGARUH FINANCIAL DISTRESS TERHADAP LIKUIDITAS SAHAM - ZANUAR FAHMI SURYA NEGARA, MOH (Jurnal Akuntansi AKUNESA, 2016)
ABSTRACT This research conducted to test the affect of financial distress to the stock liquidity. This research conducted due to a phenomenon in which company’s financial condition decreased and it might affect the investors activity in trading the shares.This research using quantitative and regression model. The sample used in this research are listed companies at Indonesia Stock Exchange that have DER > 1 during 2011-2015. The dependent variable is stock liquidity measured by Trading Volume Activity (TVA) and independent variable is financial distress measured by Altman Z-Score model.The result of this research indicates that the level of financial distress significantly have negative affect on stock liquidty that means more healthy the companies have lower stock liquidity. This indicates that investors are more active trading shares in companies which have higher financial distress rather than trading shares in healthy companies. Keyword : financial distress, stock liquidity, investor trading activity